2017
DOI: 10.1007/s11845-017-1710-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SMS (text message) reminders on attendance at a community adult mental health service clinic: do SMS reminders really increase attendance?

Abstract: The chief value of SMS reminders lies not in reminding patients of appointments but in providing a convenient way to cancel them, thus allowing more appointments to be offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
2
8
2
1
Order By: Relevance
“…To improve the cost-effectiveness of appointment reminder services, some investigators explored the value of SMS to personal mobile phones, and this strategy has been shown to have the potential in improving attendance rate in outpatient clinics. [22][23][24] In contrast to these data and the results from the current study, a previous randomized controlled trial did not demonstrate a statistically significant advantage of SMS reminders over standard care in the setting of outpatient colonoscopy. 28 The potential explanation for the difference in results are twofold.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To improve the cost-effectiveness of appointment reminder services, some investigators explored the value of SMS to personal mobile phones, and this strategy has been shown to have the potential in improving attendance rate in outpatient clinics. [22][23][24] In contrast to these data and the results from the current study, a previous randomized controlled trial did not demonstrate a statistically significant advantage of SMS reminders over standard care in the setting of outpatient colonoscopy. 28 The potential explanation for the difference in results are twofold.…”
Section: Discussioncontrasting
confidence: 99%
“…21 SMS is a programmable service that can generate reminders automatically, further increasing its costeffectiveness. This strategy has been shown to reduce missed outpatient clinic appointment, [22][23][24] but evidence in the setting of outpatient colonoscopy services is lacking. We set to conduct a prospective randomized controlled trial to evaluate the value of SMS in the quality improvement of outpatient colonoscopy services.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a Monday appointment will receive their reminder on the Friday prior to their appointment. Conclusions could not be drawn on the impact of this on patient attendance in our clinic over the study period; however, previous studies have reported on the introduction of such a system 1,11,12 …”
Section: Discussionmentioning
confidence: 94%
“…A qualitative analysis of the reasons for failed attendance found that only 23.8% of patients stated they would benefit from an SMS reminder the day before the appointment, 48.3% would prefer a phone call, 25.9% an appointment card, and only 2% would prefer email reminders 11 . Another study of the efficacy of SMS reminder systems found that failed attendance rates decreased from 22.2% to 13.9% in the first 6 months after implementation; however, after 2 and a half years since its introduction, failed attendance rates increased again to 19.3%, and no significant difference in attendance rates were found between patients who did and those who did not receive the SMS 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation